Studies on the organoleptic perception of different flavours and consumer acceptance of desiccated Chhana-murki - Shalini Arora, Ashok A Patel, Ritu Sindhu, Upasana Yadav, Tarun Pal Singh and Gaurav Chaudhary (Indian Journal of Dairy Science, 2021)
Chhana-murki is a traditional Indian nutritious dairy product manufactured by heat desiccation of paneer cubes in sugar syrup. The flavor of milk product is a key aspect that promotes its marketability. An attempt was made to add different flavors viz., Rose, pineapple, butterscotch and elaichi at different levels to enhance the likability of the formulated product. It was observed that scores for different flavors and their levels (rose and pineapple) differ significantly with rose flavored rated the maximum flavor score (8.00). The physico-chemical parameters of desiccated chhana-murki were nearer to the most favoured market sample, the values for moisture content, fat, protein, lactose, sucrose and ash content were 15.77, 15.10, 14.12, 1.41, 52.42 and 1.10 %, respectively. Further, consumer acceptance study was conducted with 180 randomly selected probable respondents and 50% consumer rated the product excellent and 51.1% consumers were willing to purchase even at a cost higher than the market price. This evidently specifies the excellent marketing potential of the developed flavored chhana-murki and the standardized technology may possibly be utilized for its upgradation at industrial scale.